2013
DOI: 10.1038/srep03061
|View full text |Cite
|
Sign up to set email alerts
|

Identification and dynamics of polyglycine II nanocrystals in Argiope trifasciata flagelliform silk

Abstract: Spider silks combine a significant number of desirable characteristics in one material, including large tensile strength and strain at breaking, biocompatibility, and the possibility of tailoring their properties. Major ampullate gland silk (MAS) is the most studied silk and their properties are explained by a double lattice of hydrogen bonds and elastomeric protein chains linked to polyalanine β-nanocrystals. However, many basic details regarding the relationship between composition, microstructure and proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
(55 reference statements)
3
39
0
Order By: Relevance
“…We note that morphologies based on ordered skin-layers and a more disordered core, providing a balance of strength and toughness, are well-known for synthetic polymeric fibers (Müller et al, 2000;Liu et al, 2014). PG-II nanodomains have only recently been suggested as functional elements, reinforcing flagelliform silk fibers (Perea et al, 2013). S,S * reflections observed for MaS fibers are probably also based on PG-II nanodomains.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We note that morphologies based on ordered skin-layers and a more disordered core, providing a balance of strength and toughness, are well-known for synthetic polymeric fibers (Müller et al, 2000;Liu et al, 2014). PG-II nanodomains have only recently been suggested as functional elements, reinforcing flagelliform silk fibers (Perea et al, 2013). S,S * reflections observed for MaS fibers are probably also based on PG-II nanodomains.…”
Section: Discussionmentioning
confidence: 82%
“…Systematic studies of nanoscale heterogeneities across the spider phylogeny should shed light on the presence and local distribution of β-sheet, PG-II and possibly other nanocrystalline inclusions. Potential targets are βtype nanodomains in Argiope decorating fibers (Figure 7B), the probably ribbon-like morphology of Eriophora MiS fibers ) and PG-II nanodomains in several flagelliform silks probed by microXRD (Craig, 2003;Perea et al, 2013). Such studies could also contribute to an understanding of the nature of graphene and single-walled carbon nanotubes inclusions in spiders MaS and silkworm fibroin fibers (Wang et al, 2014(Wang et al, , 2016Lepore et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Recently, it was shown that amorphous phase containing GGX and GPG motifs can take up polyglycine II nanocrystal structure. 140 Moreover, different types of similar secondary structures result in alternating mechanical properties. For example, in dragline silks, the tensile strength of the silk fiber is controlled by the silk primary structure, which in turn dictates the strength of interactions between β-sheets.…”
Section: Structural-mechanical Functionmentioning
confidence: 99%
“…The presence of water can greatly reduce T g as water is a known plasticizer and promotes molecular mobility (Sperling, 2005). Not surprisingly, many invertebrate silks, such as silkworm cocoon silk (P erez-Rigueiro et al, 2000;Plaza et al, 2008), lacewing silk egg stalks (Bauer et al, 2012), caddisfly net silk (Tsukada et al, 2010) and various spider silks (Gosline, Denny & DeMont, 1984;Shao, Young & Vollrath, 1999) as well as mussel byssus (Smeathers & Vincent, 1979;Troncoso, Torres & Grande, 2008), become rubberized when exposed to water, as stiffness (Young's modulus) is reduced and extensibility (breaking strain) is increased. This softening effect is believed to be the result of water molecules disrupting intermolecular hydrogen bonds (Termonia, 1994;Bauer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%